1985
DOI: 10.2527/jas1985.6161387x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Changes, Serum Iron Concentration and Performance Following Iron Injection in Neonatal Beef Calves2

Abstract: The injection of iron-dextran into beef calves at an early age immediately increased values for erythrocyte (RBC) numbers, hemoglobin (Hb) concentration, packed cell volume (PCV), mean corpuscular hemoglobin (MCH) and mean corpuscular volume (MCV), even though the calves were not anemic. There were no significant differences in average daily gain (ADG) from birth through 15 wk between those that were injected and those that were not injected. Hereford calves had lower values for PCV, Hb, MCH and MCV than Angus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
1
7
0
Order By: Relevance
“…In another study, there was no significant effect of iron injection in average daily gain from birth through 15 weeks in beef calves in comparing with those that were not received iron injection [8]. In agreement with the results of the present study, Geisser et al [10] and Sakozy et al [7] reported that, by the administration of iron, a better weight gain resulted.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In another study, there was no significant effect of iron injection in average daily gain from birth through 15 weeks in beef calves in comparing with those that were not received iron injection [8]. In agreement with the results of the present study, Geisser et al [10] and Sakozy et al [7] reported that, by the administration of iron, a better weight gain resulted.…”
Section: Discussionsupporting
confidence: 92%
“…However, Bunger et al [5] concluded that unrestricted feeding on concentrate rich in iron during colostral feeding period did not prevent Fe deficiency and believed that anemia developing in the first month of life was not physiological but was due to Fe deficiency. Numerous studies showed that the administration of iron to calves (orally or parenterally) provided an increase in hematological parameters and a better growth in calves [6][7][8][9][10][11][12][13][14][15]. On the other hand, there is a report that indicated iron supplementation (injection) had no effect on red blood cell (RBC) parameters and health of supplemented calves [16].…”
mentioning
confidence: 99%
“…However, based on available evidence [25, 33, 34], it is doubtful whether this thesis is true in patients with chronic renal failure. Both human [31, 33, 35, 36]and animal [37]studies show that the hematocrit may rise after intravenous iron administration even in the absence of anemia or iron deficiency.…”
Section: Indicationsmentioning
confidence: 99%
“…Moreover, as has been shown by both human and animal studies, hematocrit may increase after administration of intravenous iron even in the absence of anemia or iron deficiency [14, 15, 16, 17]. This observation is instructive when guiding intravenous iron use in hemodialysis patients where an increase in hematocrit after iron infusion may be interpreted as confirmation of iron deficiency.…”
Section: Introductionmentioning
confidence: 67%